72.4k views
1 vote
Y = x - 4
2x + y = 5

solve for x and y

User Oneida
by
5.3k points

2 Answers

4 votes

Answer:

X = 2

Y = 1

Explanation:

User Patrick McDermott
by
5.1k points
2 votes

Solve by substitution


y = x - 4 \\ 2x + y = 5 \\ \\ y = x - 4 \\ 2x - 5 = - y \\ \\ y = x - 4 \\ - y = 2x - 5 \\ \\ add \: the \: two \: equations \\ \\ 0 = 3x - 9 \\ 9 = 3x \\ (9)/(3) = (3x)/(x) \\ x =3 \\ \\ substitute \: 3 \: for \: x \: in \: one \: of \: the \: equations \: to \: find \: y \\ \\ y = x - 4 \\ y = 3 - 4 \\ y = - 1 \\ \\ solution \: (3. - 1)

User Keshan
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.